Integrated Topographic, GNSS, Remote Sensing and GIS/WebGIS Techniques Applied to the Study of Aquileia River Port Structures - CEFALO, RAFFAELA; COCIANCICH, ALEXIA; DI BARTOLOMEO, MICHELE; FERRO, FRANCESCA; IANSIG, MASSIMO; MANZONI, GIORGIO; Montagner, Giulio (2011)
Integrated use of multidisciplinary researches have been applied in the last years for the study of Aquileia archeological sites and, in particular the River Port structures. Since 1992 GPS (Global Positioning System) techniques have been adopted with the aim of linking together various independent topographic networks and georeferencing single relevant points. In 2001 a scientific cooperation between different Institutions and national and international Research Centres has been established and renewed in 2006, in the framework of PICS 3064 CNRS Project. Different 3D topographic, geodetic, remote sensing, laser scanner and geophysical surveys have been performed and analyzed with the principal aim of reconstructing the ancient Aquileia landscape and, in particular, the integrated water system. GIS (Geographical Information System) and WebGIS applications have been implemented by researchers of GeoSNAV Laboratory, University of Trieste, joining all the data on a common cartographic basis, in order to enhance their sharing inside the scientific community.